REPRESENTASI GAYA HIDUP REMAJA PADA VLOG AWKARIN BERJUDUL TAHUN BARUAN DI BALI BERSAMA ANYA GERALDINE - Viola Deviyanthi, Ni Wayan; Sugiarica Joni, I Dewa Ayu; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium, 2017)
Lifestyle becomes an inseperable part from the dynamic world of teenagers. This teenager’s lifestyle representation can be seen on a video blog (vlog) that can be uploaded on social media, such as Youtube. On the vlog belonging to Karin Novilda or better known as Awkarintitled Tahun Baruan di Bali Bersama Anya Geraldine (Veri Veri Explicit) was watched for 3.1 million times. The purpose of this research is to find out the representation of teenager’s lifestyle on Karin Novilda’s video blog titled Tahun Baruan di Bali Bersama Anya Geraldine (Veri Veri Explicit) . The type of this research is qualitative research with contructivist paradigm. This research used Charles Sanders Peirce semiotic analysis method. The result of this research shows that there are four type of teenager’s life style representation on this vlog, these are representation of middle-high lifestyle, hedonism, and western cultural lifestyle .   Keywords: Teenager’s Lifestyle, Video Blog Karin Novilda, Representation, Semiotics.